From Campus to Cosmos Issue 01: July 2023 - Karim, Nur Ain Syazwani; Salim, Nurul Afrisya; Esak, Nichole Heather; Sikim, Yonina (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The phrase "from campus to cosmos" is a powerful one. It represents the journey that we all take as we move from our early years on a college campus to our eventual careers in the world at large. It is a journey of discovery, growth, and transformation. On campus, we are surrounded by a supportive environment where we can learn and grow. We have the opportunity to pursue our passions, meet new people, and push ourselves. However, as we graduate and enter the workforce, we encounter additional problems. We need to learn how to negotiate the complex world of work and find our position in society. The journey from campus to cosmos is not always easy. There will be times when we feel lost or alone. But if we stay focused on our goals and never give up on our dreams, we will eventually reach our destination.